The Governance of State-Owned Enterprises in Africa: an analysis of selected cases - Mutize, Misheck; Tefera, Ejigayhu (Journal of Economics and Behavioral Studies, 2020)
Whilst some literature is of the view that; it is nearly impossible to cultivate good corporate governance culture in state-owned enterprises (SOEs), others believe that new strategies of implementing corporate governance systems together with political will can deliver SOEs out of their efficiency doldrums. This paper presents a scientific analysis of the contentious view on the possibility of creating efficient governance mechanisms in SOEs, explores the effective cost for governance failures in SOEs in Kenya, Zimbabwe, South Africa and Ethiopia. The paper makes conclusions and recommendation that the determinant factor to the success of SOEs in African countries is underpinned on the response of central government to the challenges of SOEs. Structural reforms, good governance, clear objectives and efficiency requires governments to take a decisive position. As a lasting remedial action, knowing which entities and when to offload them through privatisation, is an option in addressing the governance challenges in African SOEs. For strategic SOEs, the paper recommends that governments should consider listing them on public stock exchanges.